ANALISIS DAMPAK PELAKSANAAN CAR FREE DAY DI KOTA DENPASAR Studi kasus: Jalan Raya Puputan Niti Mandala Renon - Ni Putu Decy Arwini; I N. Widana Negara; I P. Alit Suthanaya (Master of Civil Engineering Program Study, Faculty of Engineering, Udayana University, 2015)
Abstract: Renon area is the center of the goverment system of Bali province. As one of the main street in Denpasar city, this street can represent the characteristics of Denpasar city which is the Car Free Day was held in in every Sunday morning in this street, as a simple way to reduce the air pollution and noise. The calculation in this journal is road performance, air pollution and noise level for 2 condition that is in Car Free Day and in working day. From the calculation result of road performance, the capacity of the street is 4.110 pcu/hour with degree of saturation is 0,8. The level of street service is on D category where the flow is almost unstable with high volume of traffic. The traffic volume is mostly reached the capacity and delay is frequently occur in this street. The measurement process of the level of air pollution showed that from six parameter which tested were over all are still under the standard quality which is allowed as good and medium category. The Sulfur dioksida (SO2) which was measured in busy day showed the improvement about 6,78% from the measurement which is done in Car Free Day. The nitrogen dioksida showed the improvement for about 36,35% , the carbon monoksida also showed the improvement for about 366,25%, the total dust had the greatest improvement for about 599,95% or six time greater rather than the level of total dust in Car Free Day. In the other hand, oxidantshowed the improvement for about 28,75%.The noises which occured in Car Free Day showed the average level of dB(A)is 61,65 whereas in workdays showed 72,77 dB(A). At 07.30 until 07.45 in the morning , the maximum level of noises occurs in Car Free Day and in work day. The noises improvement which occured when the Car Free Day was held with workday is about 19,17%.